2012
DOI: 10.1007/s00284-012-0105-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Gut Microbe Profiles and Numbers Between Patients with Liver Cirrhosis and Healthy Individuals

Abstract: Human liver was closely associated with gut through various biological mechanisms, such as bacterium-gut interactions. Alterations of gut microbiota seemed to play an important role in induction and promotion of liver damage progression. The aim of this study was to characterize the gut microbiota in liver cirrhosis patients and assess whether there are alterations in the diversity and similarity of intestinal flora in cirrhotic patients when compared with healthy individuals. PCR-denaturing gradient gel elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 41 publications
1
38
1
Order By: Relevance
“…Clustering analyses of DGGE profiles were performed with the NTSYS program version 2.10e (Exeter Software, Setauket, NY, USA) by scoring the presence or absence (1 or 0) of DGGE bands. The clustering algorithms used to calculate the dendrogram was an unweighted pair group method with arithmetic averages (UPGMA) (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clustering analyses of DGGE profiles were performed with the NTSYS program version 2.10e (Exeter Software, Setauket, NY, USA) by scoring the presence or absence (1 or 0) of DGGE bands. The clustering algorithms used to calculate the dendrogram was an unweighted pair group method with arithmetic averages (UPGMA) (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We failed to give a definite explain with our present study. However, Liu et al (2012) found an increased diversity of microbial composition in liver cirrhosis patients, and they speculated that it might be related to bacterial overgrowth in chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cirrhosis patients have colonic microbiota that are different from that of healthy control subjects. 10,11 Increases in Enterobacteriaceae and Enterococcus with a reduction in Bifidobacterium species were noted in one report. Whether these changes are a cause or a consequence of cirrhosis is not clear.…”
Section: Microbiota and Liver Diseasementioning
confidence: 99%
“…Whether these changes are a cause or a consequence of cirrhosis is not clear. 10 An earlier report had indicated a reduced proportion of bacteroidetes and an increase in proteobacteria and fusobacteria. 11 In fact, a positive correlation was observed between Child-Turcotte-Pugh score and streptococcaceae.…”
Section: Microbiota and Liver Diseasementioning
confidence: 99%